THE ROLE OF MANAGEMENT INFORMATION SYSTEMS IN IMPROVING OPERATIONAL EFFICIENCY IN CAFE ATEKU BUSINESSES - Jeinvanny Githa Theosendy Tarigan; Ryndian Gusty (Asian Journal of Islamic Economic Studies, 2026)
This study aims to identify the role of Management Information Systems in improving operational efficiency at Ateku Kopi Cafe, a micro-enterprise located in Medan City. Using a descriptive qualitative method through interviews and direct observation, this research examines the use of digital systems such as Luna/Mocapos for transaction recording and Google Calendar for employee scheduling. The results indicate that these systems help accelerate transaction processes, enhance the accuracy of financial reporting, and support better coordination among employees. However, several challenges remain, including manual stock management, limited system access, and insufficient digital training for staff. Overall, the implementation of Information Systems provides a positive impact on the operational efficiency of the business. Further development of an integrated system and continuous digital literacy training is recommended to improve UMKM performance amid ongoing digital transformation.